Beyond Covid-19: The Future of Festivals in Calabarzon, Philippines - Luna, Ande M.; Dizon, Josefina T.; Corpuz, Jaysi T.; Flordeliza, Myra A.; Espiritu, Patrick John S. (International Journal of Professional Business Review, 2023)
Purpose: This study aims to determine or forecast the willingness of regular participants of festivals to attend or join events festivals in the post-COVID-19 scenario. Specifically, it aimed to 1.) identify the perceived future of festivals in the post-pandemic scenario and if people are still willing to participate in or join in any of the festival's events, and 2.) discuss the role of festivals in the post-pandemic scenario.